Game development essentials with Unity 4 : LiveLessons (video training) - Geig, Mike (LiveLessons (Indianapolis, Ind.), 2012)
"Game Development Essentials with Unity 4 LiveLessons demonstrates the power and versatility of the Unity 4 engine and helps you leverage this engine in your own game development endeavors. Each lesson in this series focuses on a particular aspect of the Unity game engine, and by the end of the course, you should be able to begin making your own games. Geig covers the Unity interface, concepts of 2D and 3D game development, building terrain for your games, as well as developing game objects that interact through collision. You will also learn to work with scripts and manipulate objects through code. And for those of you who want to develop for mobile devices, you will find coverage here as well. Finally, the course ends with a lesson on how to construct your own game with the Unity 4 game engine."--Resource description page.